Modern opportunities of radiation diagnostics of small intestine diverticulosis - S. G. Burkov; N. Yu. Gurova; S. A. Vasil'chenko; N. N. Golubev; V. Yu. Melent'eva (Вестник рентгенологии и радиологии)
Diverticulosis of distal parts of a small intestine is a rare and difficultly diagnosed disease. This pathology usually is asymptomatic, and the first clinical manifestations oftenly testify the development of complications. The leading seat in the diagnosis of diverticulosis is borrowed with beam investigative techniques: ultrasonography, barium enterography, CT or MRI.In this article a brief review of clinics and possibilities of instrumental diagnosis of diverticulosis of small intestine is presented and illustrated by clinical case of a patient with large jejunoileal diverticulosis.